Higher Educational Management: Challenges and Perspectives in Small and Medium-Sized Universities in Southern Brazil - Albano, Sandro Albino; Hormazábal Soto, Auristela (Journal of Public Administration and Governance, 2022)
In contemporary Brazil, while many social changes are taking place, higher education institutions face difficulties in harmonizing the quality of education with responsible, efficient management and sustainability. This study aimed to analyze the actions of managers for corporate educational governance in private small and medium-sized universities, in the Southern region of Brazil. The investigation is qualitative, descriptive, and exploratory with primary data collected from semi-structured interviews with fifteen owners, executives, and managers of different private universities, analyzed with the content analysis technique. Our results point to educational governance as a management enhancer, as it gives direction, integrates the organization, and ensures institutional value, by monitoring and evaluating results in a sustainable way. Educational governance supports transparency, equity, and corporate responsibility. It is concluded that it is necessary to incorporate educational corporate governance with the inclusion of the principles of educational management and academic innovation together with university social responsibility to facilitate a transformative learning experience in higher education institutions.